Applying Mahmoud Shaltout’s Contextual Tafsīr to Qur’anic Teaching: Insights from Islamic Educational Institutions - Thahir, Ilyas; Akhmad Bazith; Wahyudin; Hamka Ilyas (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
Contemporary debates on contextual tafsīr (exegesis) often emphasize methodological reform, yet they pay limited attention to how such approaches are pedagogically enacted and stabilized within Islamic educational institutions. This gap is particularly relevant to the legacy of Mahmoud Shaltout, whose contextual method sought to harmonize textual fidelity with socio-historical awareness. This study investigates how Shaltout’s methodology is implemented through pedagogical sequencing in Qur’anic teaching, and how this process mediates questions of textual authority. Through a qualitative, multi-site field study, this research draws on classroom observations, semi-structured interviews with instructors and students, and document analysis across selected Islamic educational institutions. The findings reveal a patterned epistemic sequence: instruction begins with linguistic and textual clarification, proceeds to socio-historical contextualization, and culminates in ethical abstraction and contemporary application. This staged process mitigates resistance, preserves scriptural authority, and enables gradual interpretive expansion. Consequently, the study argues that contextual tafsīr attains institutional sustainability not merely through theoretical coherence, but through structured pedagogical enactments that actively negotiate authority in practice.